TI_GERICHTE 60.2005.435 vom 18. Januar 2006 , istanza di ricusa / esclusione nei confronti del presidente della Pretura penale. - TI Tribunale d'appello (2006)
istanza di ricusa / esclusione nei confronti del presidente della Pretura penale.